2006
DOI: 10.1021/la0607003
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure and Mechanical Properties of Polybutylacrylate Filled with Grafted Silica Particles

Abstract: We investigate the nanostructure and the linear rheological properties of polybutylacrylate (PBA) filled with Stöber silica particles grafted with PBA chains. The silica volume fractions range from 1.8 to 4.7%. The nanostructure of these suspensions is investigated by small-angle neutron scattering (SANS), and we determine their spectromechanical behavior in the linear region. SANS measurements performed on low volume fraction composites show that the grafted silica particles are spherical, slightly polydisper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 53 publications
5
68
0
Order By: Relevance
“…In the literature, one can find numerous references (Inoubli et al 2006;Shikata and Pearson 1994;van der Werff et al 1989;Graebling et al 1993;Watanabe et al 1996;VignauxNassiet et al 1998) on suspensions showing secondary relaxation processes which are similar to the one described in this paper. Watanabe et al (1997) discuss the frequency dependence of the storage and loss moduli G and G of spherical styrene-isoprene micelles randomly dispersed in a nonentangling homopolyisoprene matrix.…”
Section: Discussionsupporting
confidence: 72%
“…In the literature, one can find numerous references (Inoubli et al 2006;Shikata and Pearson 1994;van der Werff et al 1989;Graebling et al 1993;Watanabe et al 1996;VignauxNassiet et al 1998) on suspensions showing secondary relaxation processes which are similar to the one described in this paper. Watanabe et al (1997) discuss the frequency dependence of the storage and loss moduli G and G of spherical styrene-isoprene micelles randomly dispersed in a nonentangling homopolyisoprene matrix.…”
Section: Discussionsupporting
confidence: 72%
“…For the un-grafted system, this process would be provided by a "glassy layer" surrounding the filler [6,21,37], while for the grafted system it is given by contact between grafted layers [16,17,19,38]. These grafted layers could also be glassy, as mobility of grafted chains in the interface could be reduced [18].…”
Section: Discussionmentioning
confidence: 99%
“…Grafting polymer chains on the fillers can be used to control the internal organization in the composites and study the effect of the change in interfacial interactions on particles dispersion and mechanical properties of the nanocomposites. Recent results show that mechanical reinforcement is mainly based on the nanoparticles [15,16,17,18] (no matrix contribution), especially for individual particles dispersion in which solid-like behavior can be related to the direct contact between grafted brushes [19][20]. However, a general rule describing the mechanical behavior as a function of several particles dispersion, which can be individual, finite size aggregates (connected or not), or larger agglomerates, remains currently to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Cassagnau [41] studied the viscoelastic properties of nanosilica-filled ethylene vinyl acetate copolymer (EVA, 60 wt% of vinyl acetate) in the molten state and diluted EVA/xylene solution, finding a liquid-solid transition at Φ c = 3.3 vol%, independently from the polymer chain regimes (entangled or Rouse regime). Inoubli et al [42] observed that 2.5 vol% of silica in polybutylacrylate nanocomposite was very close to the percolation threshold. Starting from these considerations, the objective of the present work is to investigate the linear viscoelastic behaviour of silica micro-and nanocomposites in the molten state, in order to find, at least from a qualitative point of view, a correlation between the filler characteristics (size and surface area) and the resulting dynamic rheological properties.…”
Section: Introductionmentioning
confidence: 95%